Blue, Black, and Stripes: Evolution and Development of Color Production and Pattern Formation in Lizards and Snakes - Kuriyama, Takeo; Murakami, Arata; Brandley, Matt; Hasegawa, Masami (Frontiers in Ecology and Evolution, 2020)
To gain a mechanistic understanding of color pattern formation, including molecular and genetic mechanisms, it is necessary to not only describe adult phenotypes, but also to understand color production and pattern formation during embryonic and postembryonic stages. Here, we review the pigment cell mechanisms underlying color production and pattern formation during embryonic development in lizards and snakes to provide a comprehensive pigment-cell–based understanding of color pattern formation. We first focus on different color production mechanisms in terms of epidermal and dermal pigment cell architectures and then discuss the genetic determinants of pattern formation considering both biologically relevant theoretical models and the processes of pigment cell specification, migration, and architecture differentiation. Clarifying the contributions of pigment cells and genetic factors improves our general understanding of reptilian color pattern evolution.